Advanced Hepatocellular Carcinoma with Subtotal Occlusion of the Inferior Vena Cava and a Right Atrial Mass - Christian Steinberg; Suzanne Boudreau; Felix Leveille; Marc Lamothe; Patrick Chagnon; Isabelle Boulais (Case Reports in Vascular Medicine)
Hepatocellular carcinoma usually metastasizes to regional lymph nodes, lung, and bones but can rarely invade the inferior vena cava with intravascular extension to the right atrium. We present the case of a 75-year-old man who was admitted for generalized oedema and was found to have advanced HCC with invasion of the inferior vena cava and endovascular extension to the right atrium. In contrast to the great majority of hepatocellular carcinoma, which usually develops on the basis of liver cirrhosis due to identifiable risk factors, none of those factors were present in our patient.